Variations in pockmark composition at the Vestnesa Ridge: Insights from marine controlled source electromagnetic and seismic data. (24th March 2017) - Goswami, Bedanta K.; Weitemeyer, Karen A.; Bünz, Stefan; Minshull, Timothy A.; Westbrook, Graham K.; Ker, Stephan; Sinha, Martin C.
Abstract: The Vestnesa Ridge marks the northern boundary of a known submarine gas hydrate province in the west Svalbard margin. Several seafloor pockmarks at the eastern segment of the ridge are sites of active methane venting. Until recently, seismic reflection data were the main tool for imaging beneath the ridge. Coincident controlled source electromagnetic (CSEM), high‐resolution two‐dimensional (2‐D) airgun, sweep frequency SYSIF, and three‐dimensional (3‐D) p‐cable seismic reflection data were acquired at the south‐eastern part of the ridge between 2011 and 2013. The CSEM and seismic data contain profiles across and along the ridge, passing several active and inactive pockmarks. Joint interpretation of resistivity models obtained from CSEM and seismic reflection data provides new information regarding the fluid composition beneath the pockmarks. There is considerable variation in transverse resistance and seismic reflection characteristics of the gas hydrate stability zone (GHSZ) between the ridge flanks and chimneys beneath pockmarks. Layered seismic reflectors on the flanks are associated with around 300 Ωm 2 transverse resistance, whereas the seismic reflectors within the chimneys exhibit amplitude blanking and chaotic patterns. The transverse resistance of the GHSZ within the chimneys vary between 400 and 1200 Ωm 2 . Variance attributes obtained from the 3‐D p‐cable data also highlight faults and chimneys, which coincide with the resistivity anomalies. Based on the joint data interpretation, widespread gas hydrate presence is likely at the ridge, with both hydrates and free gas contained within the faults and chimneys. However, at the active chimneys the effect of gas likely dominates the resistive anomalies. Plain Language Summary: Active methane venting was observed at several seafloor locations at the south‐eastern segment of the Vestnesa Ridge in the west Svalbard margin. New geophysical data acquired in the area between 2011 and 2013 provide new constraints at understanding potential factors enabling the active venting in the area. High levels of free gas is inferred beneath the locations of known vents based on the joint analysis of multiple geophysical datasets. Key Points: Joint analysis of coincident CSEM, 2‐D and 3‐D seismic reflection data at Vestnesa Ridge Strong correlation between high‐resistivity anomaly, amplitude blanking, and chaotic seismic reflection patterns High levels of free gas and hydrate likely within active chimneys